2001
DOI: 10.1001/archotol.127.11.1375
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Choanal Atresia

Abstract: Mitomycin is an effective and reliable treatment for improving the surgical outcome for choanal atresia repair. This may obviate the need for postoperative dilations and may potentially eliminate the need for surgical stenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(22 citation statements)
references
References 23 publications
0
19
0
3
Order By: Relevance
“…This approach uses a variety of mucosal incisions exposing the hard palate. Exposure using this route is superior, but comes at the expense of removal of the posterior hard palate and midline palatal suture, resulting in delayed maxillofacial growth sequelae as well as several other adverse effects, including palatal fistulas, palatal muscle dysfunction, increased operative time, perioperative bleeding and postoperative pain [4].…”
Section: Discussionmentioning
confidence: 99%
“…This approach uses a variety of mucosal incisions exposing the hard palate. Exposure using this route is superior, but comes at the expense of removal of the posterior hard palate and midline palatal suture, resulting in delayed maxillofacial growth sequelae as well as several other adverse effects, including palatal fistulas, palatal muscle dysfunction, increased operative time, perioperative bleeding and postoperative pain [4].…”
Section: Discussionmentioning
confidence: 99%
“…To avoid that possibility, we sought a technique that would cover as much of the denuded bone as possible with normal epithelium. As granulation tissue develops mainly from the lateral borders, it was important to cover this area [11]. The endoscopic transnasal technique used here successfully preserved the mucoperichondrial flap which was used to cover about 50% of the new choana.…”
Section: Discussionmentioning
confidence: 99%
“…transpalatal approach was considered the most appropriate and successful for both BCA and UCA in children of all ages, and for revision in cases of failed transnasal procedures [13]. However, the transpalatal approach was associated with several adverse effects, including palatal fistulas, maxillofacial growth disturbances, perioperative bleeding, and postoperative pain [11]. Since 1990, some studies have reported high success rates for endoscopic techniques using either an otologic drill or conventional instruments [14][15][16], but their conclusions were based mainly on small numbers of children with UCA [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated a decrease in recurrence rate of pterygiums, benign fibrovascular growths of the conjunctiva, with the topical addition of Mitomycin C . This drug has also been shown to prevent scar tissue formation after glaucoma filtration surgery, canine subglottic surgery, pediatric choanal atresia repair, rabbit maxillary antrostomy surgery, and tracheal stenosis repair . While the biological nature of plantar fibromas is not well understood, it is generally accepted that fibroblast proliferation is the main problem .…”
mentioning
confidence: 99%